Fumaric acid esters in psoriasis and multiple sclerosis. (30th April 2014) - Zecca, C.; Caporro, M.; Adami, M.; Mainetti, C.; Gobbi, C.
Summary Fumaric acid esters (FAEs) are effective in patients with moderate to severe psoriasis. Recent studies also report the efficacy of one FAE component, dimethylfumarate, in relapsing forms of multiple sclerosis (MS). We describe the case of a patient with MS who developed severe plaque psoriasis during interferon‐β‐1a treatment for MS. The psoriasis was unresponsive to usual topical treatments and phototherapy. The patient was started on FAE 720 mg daily, with complete remission of the psoriatic lesions and neurological stabilization at follow‐up at 24 months. Our case suggests that FAEs could represent a therapeutic option for patients with MS who develop plaque psoriasis following exposure to immune‐modulating agents.